Integrating Islamic STEM Education in Elementary Science Learning: A Systematic Literature Review of Character Building and Scientific Literacy - Romi Kurniawan; Hendrizal Hendrizal; Firsty Sofila (Tarbiyah Al-Awlad: Jurnal Kependidikan Islam Tingkat Dasar, 2025)
This study identified effective models of Islamic STEM integration in elementary science learning, evaluated their impact on character building and scientific literacy, and formulated implementation recommendations. The separation between science content and Islamic values hindered holistic character development in Indonesian primary schools. The researcher conducted a systematic literature review following PRISMA protocol by analysing 28 indexed articles from 2018 to 2024 sourced from Scopus, Web of Science, and Sinta databases. Three effective integration models emerged: thematic-Quranic verses, ethics-project, and Islamic science history, yielding significant improvements in religious character (28.1%) and scientific literacy (26.5%). Project-Based Learning proved most effective (82.1%) by creating authentic learning experiences. Major barriers included lack of integrated curriculum, teachers' multidisciplinary competence, and combined learning resources. The research successfully developed the Islamic-Character and Science-Literacy Integration (IKILS) conceptual framework that positions Islamic values as the foundation of STEM education. Islamic STEM integration demonstrates feasibility and effectiveness in resolving religion-science dichotomy while shaping khalifah-character generation